Additional Evidence on the Relationship between an Internal Audit Function and External Audit Fees in Australia. (22nd April 2013) - Singh, Harjinder; Woodliff, David; Sultana, Nigar; Newby, Rick
<x xml:space="preserve">Abstract</x> Studies examining the relationship between a firm's internal audit (IA) function and its audit fees have produced mixed results with suggestions of possible model mis‐specification in these studies. Our analysis reveals that differences in significance for IA with audit fees is driven by the choice of variables proxying for firm size and other firm characteristics, suggesting that prior results are entangled with model specification issues. Specifically, when the sales variable is used as a measure of firm size, IA is insignificant (in explaining variations in audit fees) but subsequently becomes significant when assets and employees are used. To overcome the conflicting results, subsequent factor analysis supported a positive relationship between IA and audit fees. The most significant implication from this study is that previously reported relationships involving audit fees may be the outcome of the model adopted rather than the underlying relationship between the variable of interest and audit fees